(untitled) (International relations and international law Journal, 2016)
The military-political aspect of cooperation between Kazakhstan and the U.S. is one of the important fields of interaction between the states. During the first years of independence the interests of the U.S. were around the Soviet nuclear weapons located on the Kazakhstani territory. Cooperation in the militarypolitical field develops also on the structural level through NATO. After the events of September 11 the US proclaimed a war against terrorism. The struggle against terrorism became one of the major challenges of the US foreign policy. Therefore due to its geopolitical and strategic location the role of Kazakhstan increased. In this article will be made an attempt to trace the dynamics of Kazakhstani-U.S. relations in the military-political direction.